Community-Based Intervention for Malnutrition in Children Under Five: A Scoping Review - Amelia, Vira; Arief, Yuni Sufyanti; Sylvia Dwi Wahyuni (Universitas Muhammadiyah Surakarta, 2025)
Malnutrition remains a significant global challenge, especially in developing countries. This scoping review aimed to identify community-based strategies for malnutrition in children under five. The scoping review conducted herein adhered to the methodologies outlined in conjunction with the guidelines specified in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) extension for the scoping Reviews checklist. This study used three databases (PubMed, ProQuest, and Scopus) and included studies published between 2014-2024, with the search keywords